The reality of administrative training in Aseer Education Administration and the obstacles to its development from the employees’ point of view - Al-Marhi, Mona Ahmed Yahya; Al-Ghamdi, Sohair Ahmed Mohammed; Bahashwan, Nouf Saleh Saeed; Al-Abdi, Bader Saleh (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the reality and prospects of development and administrative training in the Asir Education Department according to the academic qualification and career position, and to achieve the goal, the researchers used the descriptive analytical approach, and the tool was represented in a questionnaire that included (40) phrases distributed on three axes, which were applied to a sample of (162) administrators in the Asir Education Department. The study reached several results, most notably: 1.The respondents practice training and development to a large degree (73%). 2.There were no statistically significant differences at the level of (0.05) or less between the attitudes of administrative leaders and employees in the Asir Education Department about the training process. 3. Administrative leaders and employees in the Asir Education Department agree with the training process to a large degree, by (74.3%). 4. The members of the study sample agree that there are obstacles to the development and administrative training of employees to a moderate degree, by (65%). Based on the results, the researchers recommended the study to: 1- Developing the skills of employees in the administration by providing adequate and useful courses that meet the training needs of employees.2- Evaluating the effectiveness of training courses periodically, using the method of comparing the trainee’s performance before training and after training to observe changes in information and skills and their reflection on the performance of employees, 3- Continue to keep abreast of the new in human resources sciences and work to educate employees about the importance and objectives of human resources management. 4- Workshops should be conducted for all employees in which their training needs are identified periodically and continuously. The researchers have proposed several proposals, most notably: 1. Studying the impact of management training practices on the creativity of employees in the management of Asir education. 2. A proposed vision for the development of employees working in the Asir Education Department.